Implementation of Character Education Policies on Online Learning in Elementary Schools - Linda Zakiah; Arita Marini; Maratun Nafiah (Jurnal Ad'ministrare, 2022)
Character education is integrated by the 2013 curriculum, so teachers are required to apply character education in the learning process in the classroom. The current implementation of online learning that is carried out at home is a difficulty for teachers to be able to instill character education directly into students. The purpose of this study was to be able to see what steps the teacher took in implementing character education in online learning in elementary schools. This research was conducted using a qualitative approach. Data collection techniques used are observation, interviews, and documentation. While the research data analysis techniques are data reduction, data display and conclusion drawing and verification. The results of the study indicate that the implementation of character education in the implementation of online learning can be done by teachers using the Zoom application for elementary school students and in online learning that is carried out using various methods and learning media, it is hoped that there will be an inculcation of character values of honesty, responsibility, discipline, mutual cooperation, collaboration, never give up, independent, and creative. So the implementation of character education in online learning in elementary schools can be carried out properly. This research can be used as a reference on character education in online learning in elementary schools, because previous research has focused on the high school level.